2013
DOI: 10.1371/journal.pone.0060045
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Gene Co-Expression Network Reveals Biological Functions Underlying eQTLs

Abstract: What are the commonalities between genes, whose expression level is partially controlled by eQTL, especially with regard to biological functions? Moreover, how are these genes related to a phenotype of interest? These issues are particularly difficult to address when the genome annotation is incomplete, as is the case for mammalian species. Moreover, the direct link between gene expression and a phenotype of interest may be weak, and thus difficult to handle. In this framework, the use of a co-expression netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…We performed a gene co-expression network analysis to investigate the phenotypic change of genes associated with AMI (Kumari et al, 2012; Villa-Vialaneix et al, 2013). Twelve genes from the AMI and control groups were chosen as key regulatory genes (| Dif _ Kcore | > 30), and it was shown that there was a significant change in the expression pattern of genes in the AMI group (Supplement Table 5), namely CNN2 (calponin 2), CRYZ (quinone oxidoreductase), SULT1A1 (sulfotransferase 1A1), SULT1A2 (sulfotransferase 1A2), PRMT2 (protein arginine methyltransferase 2), ATP1B1 (ATPase, Na + /K + transporting, beta 1 polypeptide), CX3CR1 (CX3C chemokine receptor 1), GCH1 (GTP cyclohydrolase 1), INSIG1 (insulin-induced gene protein), CXCL5 (C-X-C motif chemokine 5), GBP3 (guanylate-binding protein 3) and HEG1 (heart development protein with EGF-like domains 1).We hypothesized that the 12 key regulatory genes are likely to be closely related to the occurrence and development of AMI (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…We performed a gene co-expression network analysis to investigate the phenotypic change of genes associated with AMI (Kumari et al, 2012; Villa-Vialaneix et al, 2013). Twelve genes from the AMI and control groups were chosen as key regulatory genes (| Dif _ Kcore | > 30), and it was shown that there was a significant change in the expression pattern of genes in the AMI group (Supplement Table 5), namely CNN2 (calponin 2), CRYZ (quinone oxidoreductase), SULT1A1 (sulfotransferase 1A1), SULT1A2 (sulfotransferase 1A2), PRMT2 (protein arginine methyltransferase 2), ATP1B1 (ATPase, Na + /K + transporting, beta 1 polypeptide), CX3CR1 (CX3C chemokine receptor 1), GCH1 (GTP cyclohydrolase 1), INSIG1 (insulin-induced gene protein), CXCL5 (C-X-C motif chemokine 5), GBP3 (guanylate-binding protein 3) and HEG1 (heart development protein with EGF-like domains 1).We hypothesized that the 12 key regulatory genes are likely to be closely related to the occurrence and development of AMI (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Links between sub-networks and biological phenotypes of interest were investigated ( Figure 1C). To this end, methods coming from spatial statistics were used as described in [13,51]. First, the correlation between each protein expression community and the phenotype of interest was calculated.…”
Section: Proteome Network Clusteringmentioning
confidence: 99%
“…To better dissect the underlying biology behind eQTL regulation, a gene network approach was carried out to explore the 272 genes regulated by eQTL to identify communities with possible links with a pHu level (Villa-Vialaneix et al, 2013). Thereby 20 genes and especially one community of genes were identified to be correlated to pHu.…”
Section: Eqtl In Pigmentioning
confidence: 99%